(3GdefWbs - (3GdHdNj, CHh Ydj, GHf SjfG, GdQFjS, TQa Gdedc, GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG, (B428 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3GdebGdI GdChdi ef Gdaf GdChd ef GdLedI GdGhdi hgj aj Yde GdefWb aUd aj GdETGQI Edi eG jTJed Ydjg cJGH (B... (3aEf ZQVfG aj gPG GdcJGH GdPj fQLh Cf jegdfG GdReGf Edi NJeg hjUMHfG GdJhajb ef Gddg (B...s
(3BNQgG (B:s
... (3eKd Cf GdfeQ dG jTGQc GdCSO aj Gdche hjTGQcg aj YXe GdCWQGa GdYGdjI heY Pdc jTGQcg aj GdTLGYI adhf YXe GdGWQGa GdYGdjI OdjdG hYdGeI ddTLGYI Ohf GddRe aEf jLH Gf jchf GdhGSWI aj GdaQGSI Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\241s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs